Disabled childern in public playgrounds : a pilot study / Seyed Hassan Khalifeh Soltani, Mohamed Yusoff Abbas and Mohamad Awang - Khalifeh Soltani, Seyed Hassan; Abbas, Mohamed Yusoff (Faculty of Architecture, Planning and Surveying, 2013)
This is a cross-sectional pilot study on children with disabilities needs in public playgrounds. They often faced problems at public playgrounds, entertainment and amusement areas, due to the lack of ample provisions to cater their special needs.